Osteopathy: Italian professional profile. A professional commentary by a group of experts of the European community of practice. (June 2021) - Cerritelli, F.; Lunghi, C.; Esteves, J.E.; Vaucher, P.; van Dun, P.L.S.; Alvarez, G.; Biberschick, M.; Wagner, A.; Merdy, O.; Menard, M.; Tavernier, P.; Clouzeau, C.; et al.
Abstract: Osteopathy became recently regulated as a healthcare profession in Italy. The Italian legislation classifies osteopathy as a healthcare profession, which focuses on health prevention and maintenance with a role in rehabilitation and functional psychosocial recovery. The legislative framework also lays down the osteopathic professional profile. Osteopaths are described as healthcare practitioners who deliver osteopathic person-centered care focused on the musculoskeletal system and the concept of somatic dysfunction. Despite these positive developments in the legislation for osteopathy, the Italian law raises critical points regarding the validity of osteopathic care models, namely the concept of somatic dysfunction and the role of osteopaths in health promotion and prevention. The legislative developments currently occurring worldwide must be informed by a critical appraisal of osteopathic conceptual models and grounded on robust research. In the article, a panel of European osteopaths involved in clinical and academic practice, research and regulation, present this professional commentary to facilitate a critical discussion on the role, competencies and scope of practice of osteopaths in the light of the recently published Italian osteopathic professional profile.